(untitled) (Studia Prawnicze / The Legal Studies, 2016)
Ochrona praw małoletnich, zwłaszcza przed seksualnym wykorzystaniem i związaną z nim przemocą, jest szczególnie istotnym elementem w systemie ochrony praw człowieka. Zagadnienie to pojawia się zarówno w licznych aktach prawa międzynarodowego, jak i na forum krajowym. Świadczą o tym częste w ostatnich latach zmiany w prawie karnym, polegające na tworzeniu nowych typów czynów zabronionych oraz nowelizacjach przepisów dotyczących przestępstw seksualnych, a także przyjmowaniu programów zapewniających wsparcie ofierze przestępstwa seksualnego oraz terapii wobec sprawców tego rodzaju przestępstw. W związku z tym nieustannie trwają także poszukiwania skutecznych sposobów przeciwdziałania przestępczości seksualnej. The article discusses on the Act on counteracting threats of sexual offences. It introduces to the Polish legal system the Registry of Sex Offenders in a version with a limited access and a version available to the public. Criticising the adopted solutions, the author point out the lack of integration with other interventions conducted in Poland against sex offenders, noncompliance with the recommendations of the most important expert circles in the field. The summary emphasises that access to information contained in the registry of limited access will increase the safety of children, especially in those areas where the authorities of the state or local government shall perform activities related to the wider education, treatment or care of minors. However, it should be connected with the organization of a wide range of preventive measures. From the other side the public registry will contribute to increasing public concerns and will be associated with the negative consequences for the perpetrators, and often their families, and the victims themselves. There is certainly an effective instrument that can be used countering threats of crime against sexual abuse.